PERCOBAAN PENDAHULUAN MENGGERGAJI BATANG KELAPA - Osly Rachman; S Karnasudirdja (Jurnal Penelitian Hasil Hutan, 1984)
Fourteen   air  dry   logs  of   coconut   trunk   were  sawn  into   boards  and  squares of  varying  dimensions  following   a "sawing  around"   pattern   to  obtain   the  best  lumber  yield  from the hard outer portion of the trunk. A 43.16 percent yield was obtained.                                                                                                                                          The productivity  of  break down  saw based on  the optimum  feed  speed  of  8.67  meters  per  minute   was  0.0542 m3 per minute. Only saw blades hardened by stellite tipping are recommended for sawing coconut trunks.